If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 6 = 0 Reorder the terms: 6 + n = 0 Solving 6 + n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + n = 0 + -6 Combine like terms: 6 + -6 = 0 0 + n = 0 + -6 n = 0 + -6 Combine like terms: 0 + -6 = -6 n = -6 Simplifying n = -6
| 2(c+5)+3(2c+2)=2+2(3c+10) | | 7(1-3m)=39+2m | | 6.5=2.5t-11 | | 80000-.25x=x | | -x-6(x+8)=-36-4x | | t(4-1)+9=27 | | 5(2+3w)-1=-6 | | 5(2z-1)-4(z+3)=4(z+1) | | 6(6+6v)=36-v | | (2+3w)-1=-6 | | 6y=5 | | (x+2)(x-2)=1 | | -28=196x | | 80000-2x=x | | -6x+4x=-12 | | 8.69=-1-4.7x-x | | 5(2z-1)-4(2+3)=4(2+1) | | 4x=-1+2(x+1) | | 14-(x+5)=4x-6 | | 8-5x=x-16 | | 2(x+3)-5[4-(x-6)]=x+2 | | 4+9=-8+-13 | | 2x+8y=24 | | 4y-6=-2y-11 | | xsuared=x-6 | | -2(5n+2)=4 | | -2.25=-2.6x+0.16 | | g/10+14=5 | | 3(5a-4)= | | 4(3.14)=w-6(3.14) | | 8+3t=4 | | 4x+2y=250 |